Nutrient Supplementation: Improving Male Fertility Fourfold - Mora-Esteves, Cesar; Shin, David (Seminars in Reproductive Medicine, 2013)
Oxidative stress can contribute to impairment in spermatogenesis leading to male-factor infertility. The effectiveness of various antioxidants (such as carnitine, vitamin C, vitamin E, selenium, carotenoids, glutathione, N-acetylcysteine, zinc, folic acid, and coenzyme Q10) is variable with respect to improving semen parameters and pregnancy rates. A recent Cochrane review determined that men taking antioxidants had a statistically significant increase in both live birth rates and pregnancy rates. For those undergoing assisted reproduction, the odds ratio that antioxidant use would improve pregnancy rates was 4.18, with a 4.85-fold improvement in live birth rate also noted. Further investigation with randomized, controlled clinical trials is needed to confirm the safety and efficacy of antioxidant supplementation in the medical management and treatment of male infertility.
Keywords: male infertility; antioxidant therapy; vitamin supplements; oxidative stress